Wojenne losy Heleny Grossówny - Pieńkowska -Wyżyńska, Beata; Wyżyński, Adam (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
Helena Grossówna, one of the most popular prewar Polish actresses, at the peak of her popularity got confronted with wartime. Like most people of art after 1st September 1939 she abandoned hitherto lifestyle and participated in the defense of Warsaw as a nurse and cook but did not become a regular soldier at that time. Together with other professional jobless actors she rendered services as a waitress in a café U Filmowców and occasionally performed on a stage. However, in the third year of war she joined the structures of Polish Underground State and fought in the Warsaw Uprising in Battalion Sokół. Consequently Grossówna got sent to POW camp Gross-Lübars and the latter in Oberlangen. After the camp was released in 1945, she came back to the country to struggle with the reality of Poland ruled by the Communist Party.